Multimorbidity, disadvantage, and patient engagement within a specialist homeless health service in the UK: an in-depth study of general practice data. Issue 3 (2017) - Queen, Anton B; Lowrie, Richard; Richardson, Janice; Williamson, Andrea E
No abstract available